2021
DOI: 10.3390/ma14102485
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Structural Factors Favouring Bacterial Adhesion on Orthodontic Adhesive Resins

Abstract: Bacterial adhesion to the surface of orthodontic materials is an important step in the formation and proliferation of plaque bacteria, which is responsible for enamel demineralization and periodontium pathologies. With the intent of investigating if adhesive resins used for bracket bonding are prone to bacteria colonization, the surface roughness of these materials has been analyzed, combining information with a novel methodology to observe the internal structures of orthodontic composites. Scanning electron m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The colonization of biofilm around the excess orthodontic adhesives could increase the risk of developing white spot lesions around the brackets [77,78]. Meticulous oral hygiene and various additional oral health care products [79,80] are essential to help control plaque accumulation during fixed orthodontic treatments.…”
Section: Antibacterial Action On S Mutansmentioning
confidence: 99%
“…The colonization of biofilm around the excess orthodontic adhesives could increase the risk of developing white spot lesions around the brackets [77,78]. Meticulous oral hygiene and various additional oral health care products [79,80] are essential to help control plaque accumulation during fixed orthodontic treatments.…”
Section: Antibacterial Action On S Mutansmentioning
confidence: 99%
“…This may subsequently lead to severe tooth infection/pain, complicating the orthodontic treatment. It was reported that the irregular surfaces of excess orthodontic adhesives promoted the accumulation of dental biofilms 3 . Hence, adhesives that offer remineralization and antibacterial actions may be needed to reduce the risk of dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…Bisco and Leone, which have instead shown a greater tendency to remain adherent to the enamel surface, have to be mechanically removed from the tooth by mechanical milling, taking care not to damage the dental enamel. It has been observed that, the resin tags that remain on the enamel surface, for a long time after the bracket debonding, can change colour as well as constitute sites for bacterial adherence [ 54 ]. Finally, the FE-SEM images however show a good performance of the Ovation bracket in most of the samples examined.…”
Section: Discussionmentioning
confidence: 99%